Genes de resistencia a quinolonas de localización plasmídica en enterobacteriaceae - Rincón Cruz, Giovanna (2015)
Since 1998 a number of plasmid-mediated quinolone resistance (PMQR)\ndeterminants have been reported, including the enzyme aminoglycoside\nacetyltransferase (Aac (6')-Ib-cr) variant, the efflux pumps (QepA and OqxAB),\nand the Qnr-type proteins. However, and despite numerous reports of quinolone\nresistance, there are few studies related to PMQR.\nOur main objective was to investigate PMQR prevalence in three collections of\nEnterobacteriaceae resistant to third-generation cephalosporins (RCTG)\nisolated from clinical specimens in Argentina (A), Peru (P) and Colombia (C)\nand one Colombian collection susceptible to these antibiotics.\nThe most prevalent PMQR were aac(6')-Ib-cr (A= 38.6%, P= 55.5%, Cresistant=\n71.4% and C-susceptible= 18.7%) and qnrB (A= 36.8 %; P= 25.9 %,\nC-resistant= 52.4% and C-susceptible= 3.1 %). The qepA1 allele was found in\ntwo out of three qepA positive isolates (one from each country). The third was a\nnew allele with 99% identity to qepA1 and qepA2.\nThe oqxAB genes were detected in E. coli from Perú and they were associated\nto IS6 family insertion sequences harboring in plasmids from 90 to 100 kb.\nSignificant resistance to quinolones and fluoroquinolones was shown in RCTG\nisolates, along with a high prevalence of PMQR genes. Differences in frequency\nof PMQR were observed between RCTG and sensitive isolates. This work is the\nfirst description of prevalence of PMQR genes in RCTG isolates from Argentina,\nPeru and Colombia; moreover, it is the first description and characterization of\nthe qepA and oqxAB in clinical isolates from each origin country.